Arthroscopic Volar Capsuloligamentous Repair - del Piñal, Francisco (Journal of Wrist Surgery, 2013)
Background The palmar aspect of the capsuloligamentous complex of the wrist is relatively inaccessible to surgery through an open approach. An all-inside arthroscopic suturing technique is presented that allows suturing of the palmar scapholunate or lunotriquetral ligaments or plication of the space of Poirier.Methods Eight palmar scapholunate ligaments and four major tears of the volar capsuloligamentous complex of the wrist due to a perilunate dislocation have been repaired.Results No complications occurred during or after the procedure. It was not possible to separate the effects of the palmar repair from the disparate treatment of the associated pathology.Conclusions The technique described allows one to suture the palmar aspects of the SL and LT ligaments safely and to repair the space of Poirier structures without need for any special equipment.
Keywords: wrist arthroscopy; scapholunate ligament repair; space of Poirier; all-inside technique